A Comprehensive Review on the Behaviour of Motorcyclists: Motivations, Issues, Challenges, Substantial Analysis and Recommendations - Abdulwahid S.N.; Mahmoud M.A.; Zaidan B.B.; Alamoodi A.H.; Garfan S.; Talal M.; Zaidan A.A. (MDPI, 2023)
car use; information and communication technology; public transport; traffic management; transportation safety; driving ability; experimental study; filtration; human; human experiment; motivation; motorcyclist; questionnaire; review; ScienceDirect; Scopus; sociology; systematic review; taxonomy; Web of Science; car driving; Automobile Driving; Motivation